2012
DOI: 10.1177/1475090212437627
|View full text |Cite
|
Sign up to set email alerts
|

Simple hydroelastic impact models for water-borne debris

Abstract: Debris driven by tsunamis pose a significant threat to structures, and yet most building codes that include debris impact are based on rigid-body dynamics. However, the debris will most likely not be rigid compared to the structural components, such as walls and columns, that they impact. Impact by flexible, water-borne wood poles and shipping containers is considered in this paper. A relatively simple one-dimensional model for acoustic wave propagation, for which an analytical solution is obtained, is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This was confirmed by a relatively crude but conservative inclusion of the fluid in the numerical model, which showed that the time duration of impact was too short for the fluid to contribute to the impact force [14,15], One of the goals of the experimental program was to determine the significance of the fluid for other impact scenarios, the results of which will be discussed subsequently. The debris is represented as a continuous rod (longitu dinal impact) or a continuous beam (transverse impact) traveling at an initial velocity that impacts a spring, which represents a struc tural member such as a column as well as the localized impact stiffness.…”
Section: Analytical Modelsmentioning
confidence: 91%
See 1 more Smart Citation
“…This was confirmed by a relatively crude but conservative inclusion of the fluid in the numerical model, which showed that the time duration of impact was too short for the fluid to contribute to the impact force [14,15], One of the goals of the experimental program was to determine the significance of the fluid for other impact scenarios, the results of which will be discussed subsequently. The debris is represented as a continuous rod (longitu dinal impact) or a continuous beam (transverse impact) traveling at an initial velocity that impacts a spring, which represents a struc tural member such as a column as well as the localized impact stiffness.…”
Section: Analytical Modelsmentioning
confidence: 91%
“…(1)-(3) can be obtained by either the method of characteristics [14] or mode superposition [15,16]. The analytical solution of Eqs.…”
Section: Prototypical Debrismentioning
confidence: 99%